Energy Based Food Security Assessment In Nepal - Paudel, Surya P; Shivakoti, Sabnam (Journal of Agriculture and Environment, 2013)
The basis of total edible cereal production of the district, the total population and the food requirement (Kcal/person/year) has been the basis for delineating food insecure districts. Many interventions of food security and food aid programs are mostly directed to those districts on this basis. The major objective of this paper is to assess the food security from energy production point of view considering the total energy from cereals, potato, vegetables, milk and meat. The data is based on the publication of MOAC. It was found that Nepal is sufficient in terms of energy adequacy although the situation for Terai, Hills and Mountain are different. Terai, known for its food basket, was not found better than hills in terms of food energy production required for their districts. Although Nepal has been energy adequate, the prevalence of chronic malnutrition shows the need for different intervention. In addition, Nepal suffers from protein energy malnutrition (PEM), which clearly indicates the need for crop diversification. Current food-security assessment methodology needs to be revisited and redefined. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 127-131 DOI: http://dx.doi.org/10.3126/aej.v12i0.7572